METHODS OF EFFECTIVE MANAGEMENT OF CREDIT INSTITUTION AT THE PRESENT STAGE - M. Bobrova; E. Matushina; M. Sazonova (Вестник университета)
A number of scientific and practical aspects of assessment of efficiency of activity of commercial bank is considered. On the basis of the conducted research authors gives offers on increase in bank income and decrease in risk on the basis of banking products with the built-in options. By results of the conducted research the conclusion on influence of change of a key interest rate on income of commercial banks at management of liquidity in the conditions of percentage risk. Methods of modeling of interest income of bank are presented.